Germany’s Labour Market at a Turning Point - Holger Bonin; Ulf Rinne (Wirtschaftsdienst)
Abstract The COVID-19 pandemic and the Ukraine war mark a turning point for the German labour market. These crises accelerate transformative forces that have been at work for some time, such as digitalisation and decarbonisation, and are likely to permanently change the international division of labour and mobility. The shortage of skilled workers, which already hampered development ahead of the crisis, has now grown into a broader labour shortage and has also reached the low-wage sector. This article outlines how labour shortages could be countered by concerted action from the supply and demand sides. It shows that coping with the changes in the German labour market requires more efforts from policymakers, firms and the labour force.